2022
DOI: 10.3847/1538-4357/ac98b3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolutions and Quasiperiodic Variations Present in the Sunspot Number and Group Sunspot Area Data Measured at Kodaikanal Observatory for Solar Cycles 14–24

Abstract: The Kodaikanal Observatory has made synoptic observations of the Sun in white light since 1904, and these images are sketched on the Stonyhurst grids called Sun charts. These continuous hand-drawn data sets are used for long-term studies of the Sun. This article investigates temporal and periodic variations of the monthly hemispheric sunspot number and sunspot group area for 1905–2016, covering solar cycles 14–24. We find that the temporal variations of the sunspot number and group area are different in each h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…The best known mid-term oscillations (MTOs) are the so-called quasi-biennial oscillations, QBO (see, for example, the comprehensive review by Bazilevskaya et al, 2014, and references therein). Another mid-term periodicity that was reported is sixyear oscillations (Prabhakaran Nayar et al, 2002;Ravindra et al, 2022). These variations are observed even in the full magnetic field of the Sun in "as a star" observations (Rivin and Obridko, 1992).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The best known mid-term oscillations (MTOs) are the so-called quasi-biennial oscillations, QBO (see, for example, the comprehensive review by Bazilevskaya et al, 2014, and references therein). Another mid-term periodicity that was reported is sixyear oscillations (Prabhakaran Nayar et al, 2002;Ravindra et al, 2022). These variations are observed even in the full magnetic field of the Sun in "as a star" observations (Rivin and Obridko, 1992).…”
Section: Discussionmentioning
confidence: 83%
“…The wavelet analysis is a useful tool for examining the presence of localized oscillations, both in time and frequency domains. For this time series, we have considered ω 0 (non-dimensional frequency) as 12 for mid-term frequency (low periodic zone) and 6 for the low-frequency range (long periods) (Torrence and Compo, 1998;Ravindra, Chowdhury, and Javaraiah, 2021;Ravindra et al, 2022;Chowdhury et al, 2022, etc.,). The cone-of-influence (COI), where the wavelet power reduces by a factor e −2 due to edge effect, is plotted with a bold dashed line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The white-light photographs of the Sun have been captured on photographic plates at the KSO since 1902 (Pucha, Hiremath, and Gurumath, 2016;Ravindra et al, 2022;Priyadarshi et al, 2023). A 15 cm lens mounted on the front of the equatorial telescope projects the picture of the Sun onto the screen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on solar observations show that the amplitude of the QBOs varies with the activity cycle, with the highest amplitudes during solar maxima that become weaker during the activity minima. During most solar cycle maxima, double peaks (with a Gnevyshev Gap) are more prevalent in activity indices, due to the asymmetry between the northern and southern hemispheres (Norton & Gallagher 2010;Ravindra et al 2022), where one hemisphere achieves the maximum amplitude earlier than the other hemisphere. It is also suggested that the solar cycle may evolve independently in the two hemispheres (e.g., Veronig et al 2021), which introduces asymmetry in both hemispheres.…”
Section: Introductionmentioning
confidence: 99%